95.6k views
3 votes
Use the quadratic formula to find the solutions to the quadratic equation below x^2-6x-5=0

User Mlohbihler
by
5.7k points

2 Answers

2 votes

Final answer:

The quadratic equation
x^2 -6x-5=0 is solved using the quadratic formula to find its solutions, giving the answers x = 3 +
√(14) and x = 3 -
√(14).

Step-by-step explanation:

To solve the quadratic equation
x^2 -6x-5=0 using the quadratic formula, we first identify the coefficients a, b, and c from the general form a
x^2+bx+c=0. In this case, a=1, b=-6, and c=-5. The quadratic formula is:

x = (-b ±
√((b^2 - 4ac)) / (2a))

Plugging these values into the formula gives us:


x = (-(-6) ± √(((-6)^2 - 4(1)(-5))) / (2(1))) \\x = (6 ± √((36 + 20)) / 2) \\x = (6 ± √((56)) / 2) \\x = (6 ± √((4*14)) / 2) \\x = (6 ± 2√(14) ) / 2\\x = 3 ± √(14)

Therefore, the solutions for the quadratic equation are x = 3 +
√(14) and x = 3 -
√(14).

User Mathieu Urstein
by
6.0k points
6 votes

Answer:


\large\boxed{x=3-√(14)\ \vee\ x=3+√(14)}

Step-by-step explanation:


x^2-6x-5=0\qquad\text{add 5 to both sides}\\\\x^2-6x=5\\\\x^2-2(x)(3)=5\qquad\text{add}\ 3^2\ \text{to both sides}\\\\x^2-2(x)(3)+3^2=5+3^2\qquad\text{use}\ (a-b)^2=a^2-2ab+b^2\\\\(x-3)^2=5+9\\\\(x-3)^2=14\to x-3=\pm√(14)\qquad\text{add 3 to both sides}\\\\x=3-√(14)\ \vee\ x=3+√(14)

User Madtyn
by
7.0k points